Professors Call it Cheating, Students Call it Teamwork - Jeffrey Walsh; Jessie Krienert; Kevin Cannon; Samuel Honan (Journal of the Scholarship of Teaching and Learning)
Implementation of online education pedagogy and practice has expanded rapidly at colleges and universities in recent years, most notably in response to COVID-19. This innovative teaching/learning modality provides benefits to both faculty and students through dynamic teaching/learning content, immense flexibility, and technological investments to support teaching and learning. Academic dishonesty in higher education is a persistent concern emphasized and extensively explored in traditional face-to-face courses, less so in online learning environments. The present work, drawing on a large sample of students and faculty (n=1,640) at a Midwestern university, employs an esurvey and both qualitative and quantitative responses on cheating behavior in the emergent area of online courses/online education. Results expose significant faculty and student disagreement and uncertainty about cheating behaviors in the online environment. Academic integrity is essential to fair and equitable high-quality higher education. The stakes are high to better understand the transformative shifts in academic dishonesty occurring in the online educational environment.